AB0127 Resolution of Inflammation is Associated with an Inversion of the Synovial Tissue M1/M2 Ratio in the Antigene-Induced Arthritis Model. (9th June 2015) - Gahier, M.; Boutet, M.A.; Amiaud, J.; Heymann, D.; Blanchard, F.; Le Goff, B.
Abstract : Background: Macrophages play a major role in the pathogenesis of rheumatoid arthritis (RA). There are professional phagocytic cells present in all organs to maintain tissue integrity, clear debris, and respond rapidly to initiate repair after injury. These cells can produce inflammatory cytokine such as TNF α. They can differentiate into two sub-populations: the proinflammatory M1 and anti-inflammatory M2 macrophages. It has been suggested that chronic inflammation could be enhanced by an imbalance between these two subpopulations with and excess of M1 over M2 polarization. Objectives: The goal of our work was to study the kinetic and pattern of infiltration of these cells in the synovial tissue during the course of arthritis. Methods: We used a murine animal model of antigen-induced arthritis (AIA), which is characterized by an acute arthritis followed by a spontaneous resolution of inflammation over time. Sixteen C57BL/6 mice aged 7 weeks were used. They were sacrificed at various clinical stages of arthritis: early (D3), peak (D7), stabilization (D10) and decline (D14). Expression of M1 and M2 markers within the joint was studied by RT-qPCR using the following markers: CD11b (myeloid cells), CD64 and CD86 (M1), CD163, IL-10 and CD200R (M2). The different macrophage subtypes were studied by immunohistochemistry (IHC) using the following markers: Iba-1 (pan-macrophage or M0), iNOS (M1), CD206 (M2). Finally, human synovial samples from RA patients (n=19) were using the following markers: CD68 (M0), iNOS (M1), CD163 (M2). Results: In the AIA model, the expression of CD11b was significantly increased over time. M1 markers expression was significantly increased early, on D3 (4 and 7 times for CD86 and CD64, respectively) then slowly decreased without returning to baseline (2.5 and 4 times on day 14 for CD86 and CD64, respectively; p≤0.05). Expression of the M2 markers (IL-10, CD200r1 and CD163) was modulated differently. CD163 marker decreased by 5 times at D3 (p=0.05), and quickly returned to its basal expression. The IL-10 marker increased more gradually with maximum expression of 5.5 times on D7 (p≤0.05). Finally, the marker CD200r1 increased in the early phase D3 (p≤0.05), stabilized and then decreased in decline D14. On IHC, INOS staining (M1) was maximal on D7 (score 10, p≤0.05) and decreased over time. The CD206 marking (M2) increased progressively to its maximum on D14 (score 7; p≤0.05). In human synovial biopsies intensity iNOS marking (M1) but not CD163 (M2) was correlated with the histological inflammation (p=0.0091; r =0.5806). In contrast, presence of M2 macrophages was associated with fibrinoid necrosis (p=0.002 and correlation coefficient r =0.7606). Conclusions: We did not find any real switch M1/M2 over time but a "cohabitation" of these two macrophages sub-types. However, an earlier increase in the M1 population and an inversion of the ratio M1/M2 in the resolution phase of arthritis as been observed in the AIA model. In human synovial tissues the correlation between the fibrinoid necrosis and the presence of subpopulation M2 might be linked to the functional role of these cells in tissue repair and cleaning of debris. Disclosure of Interest: None declared